The Social and Humanitarian Imperatives for Ensuring Sustainable Development in The Context of National Security - Emanov, Vladislav; Sporyshev, Kostiantyn; Stoliar, Yurii; Berezynskyi, Leonid; Trobiuk, Volodymyr (Journal of Management World, 2025)
The main purpose of the article is to form an effective methodological approach to identifying key social and humanitarian imperatives for ensuring sustainable development and the level of their influence. The object of research is the system for ensuring the sustainable development of Ukraine. The scientific task is to identify key social and humanitarian imperatives and assess their impact on sustainable development through the established methodological approach. The methodology includes the method of semantic networks in synthesis with the method of predicate language construction. At the same time, a formalized description method was used. Recommendations were made on the impact of one of the key imperatives As a result of the conducted research, a scheme of mutual understanding of imperatives and a matrix of priorities that were most significant for Ukraine were formed. The obtained result is extremely important for information support of national security and sustainable development. Possible limitations of this study include the specificity of the context, in particular, that key socio-humanitarian imperatives were largely associated with military action, which is typical for the situation in Ukraine, but may not be common in other countries. Future research prospects may include expanding the analytical framework to include additional imperatives and factors that may impact sustainable development and national security in a changing global context.